Status of package insert guidelines for drugs accessible as over the counter drugs - Jha, Anuja; Joshi, Usha; Hishikar, Rajesh; Agrawal, Manju; Halwai, Ajay (International Journal of Basic & Clinical Pharmacology, 2018)
Background: As per Indian pharmacopoeia, package inserts are part of a label that provides information on the article. It may be the sole source of information for drugs, which are available in the pharmacies without the prescription and it may include both prescription and over the counter (OTC) drugs. So, to aid in safety and efficacy of these drugs, package inserts must follow the standard guidelines (The Drugs and Cosmetics rule, 1945). The objective of this study was to observe the status of the standard guidelines for package insert in drugs accessible as OTC drugs. Methods: Based on the inquiries made with pharmacies, list of drugs commonly bought without prescription was made. 256 drugs were evaluated. Their package inserts were observed for the extent to which the guidelines given by The Drugs and Cosmetics rule 1945, section 6.2 and 6.3 are being followed. Secondary objectives were made to assess if package inserts are physician friendly or patients friendly. Results: Package inserts were missing in 180 (70%) of the drugs. Therapeutic indications were present in 71% of the available package inserts (76). Pharmaceutical information was given in 57% of the package inserts. English was the preferred language and medicinal terms were used. Only one package insert was patient friendly. Conclusions: Package inserts should be made available in every drug. There should be a separate patient oriented package insert guideline, as per US food and drug administration (FDA), in India as well. This will aid in their safe and effective use.